(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
It is known that in life, the negative actions-characteristics that human beings do knowingly come back and become a big problem for themselves. In fact, the fact that immorality, degradation of moral qualities is the cause (determinant) of global problems is presented by the authors in the article as a dialectical truth based on scientifically proven facts.